Measuring the implementation of student-centered teaching strategies in lower- and upper-division STEM courses. Issue 4 (2nd October 2021) - Benabentos, Rocio; Hazari, Zahra; Stanford, Jennifer S.; Potvin, Geoff; Marsteller, Pat; Thompson, Katerina V.; Cassone, Vincent M.; Murasko, Donna; Kramer, Laird
Abstract: Understanding the rate at which STEM faculty move from traditional, lecture-intensive teaching practices to more effective, student-centered practices and the institutional conditions that favor this shift are crucial for supporting faculty change. This study investigated the instructional practices of biology, chemistry, and physics faculty at research-intensive institutions and explored the institutional structures that support student-centered instruction. Faculty members (N = 1, 456) from 66 institutions reported on their frequency of use of a variety of instructional practices (at two time points within the last five years) and the support structures present at their institution using the Change in Implementation of Pedagogical Practices (ChIPP) survey. An index was created for measuring use of student-centered instructional strategies at these two time points, providing a measure of change over time. About 30% of all respondents reported increases in the frequency of student-centered teaching strategies over time. For all faculty, participation in institutional faculty communities was predictive of change toward student-centered pedagogies. Faculty teaching lower-division courses were more likely to use at a higher number of student-centered strategies every class, compared to their upper-division colleagues. Factors associated with greater use of student-centered strategies in lower-division courses were institutional financial opportunities for course reform, use of classrooms designed to promote active learning, and engagement in STEM education research. Only one factor, engagement in professional development, was associated with greater use of student-centered strategies in upper-division courses. These findings suggest that pedagogical change is occurring at research-intensive institutions and may be fostered through specific support structures.